Psychometric properties of a short form of the Adolescent Stress Questionnaire (ASQ-14). - Blanca-Mena, María José; Escobar-Espejo, Milagros; Lima-Ramos, Juan Francisco; Byrne, Donald; Alarcón-Postigo, Rafael (Colegio Oficial de Psicólogos del Principado de Asturias, 2020)
Background: Exposure to minor stressors is related to a range of emotional and behavioral problems in adolescents. The purpose of this study was to develop a screening instrument for assessing adolescent stressors. Method: The Adolescent Stress Questionnaire (ASQ-14) was tested on a sample of 561 adolescents aged between 12 and 18. We report validity evidence based on its internal structure (confi rmatory factor analysis) and on relationships between ASQ-14 scores and other variables (correlational analysis), as well as an estimation of score reliability and differences by sex and stage of adolescence. Results: CFA indicated a one-factor structure with a total score representing a measure of cumulative minor stressors. This structure showed an adequate fi t across all age groups (early, middle, and late adolescence). Values of internal consistency (.85) and test-retest reliability (.81) were also satisfactory. Validity evidence based on relationships with other variables showed positive relations with stress manifestations, anxiety, depression, and emotional and behavioral problems, and a negative association with life satisfaction. Finally, girls scored higher than boys, and stress scores increased across stages of adolescence. Conclusions: These results support the psychometric adequacy of the ASQ-14 and its use as a time-effi cient tool in educational, clinical, and research studies.
Política de acceso abierto tomada de: https://www.psicothema.com/PublicationNorms2022.pdf (p. 4)
Keywords: Estrés (Psicología); Adolescentes - Psicología; Adolescence; Stressors; Assessment; Screening